Rethinking the Allocation Problem and the Underlying Image of Man that Supports It - Mischel, Kenneth (Journal of Income Distribution®, 1996)
This paper calls into question the adequacy of the metaphor that the institutions endemic to a society form a social contract, conformed to and created by autonomous individuals for the sake of mutual benefit, as a basis upon which to build understandings of institutions and their change. A counterexample to Demsetz’s theory of the development of property rights, a pillar of the “new” institutional economics and exemplar of the use of the metaphor, is developed. Assessment of the metaphor has been hampered by the lack of a common framework and a common language, within the context of which discussion between its supporters and critics might fruitfully proceed. Accordingly, the case against the metaphor is made while adopting the assumptions, terminology and methods of those who typically support it.